Cost-Effectiveness Analysis of Fixed-Dose Tiotropium/Olodaterol versus Tiotropium for COPD Patients in China - Lan Y; Yang N; Wang Y; Yang Y; Xu M; He Q (International Journal of COPD, 2023)
Ying Lan,1 Nan Yang,2 Yirong Wang,1 Yan Yang,1 Min Xu,1 Qin He1 1Department of Pharmacy, Affiliated Hospital of Southwest Jiaotong University, the Third People’s Hospital of Chengdu, Chengdu, Sichuan, 610031, People’s Republic of China; 2West China School of Pharmacy, Sichuan University, Chengdu, People’s Republic of ChinaCorrespondence: Ying Lan, Email lanying0212@126.comPurpose: Tiotropium/olodaterol (TIO/OLO) fixed-dose combination (FDC) can improve lung function and quality of life for patients with chronic obstructive pulmonary disease (COPD), and is not inferior to other LAMA/LABAs. The aim of this study was to assess the cost-effectiveness of TIO/OLO FDC in patients with moderate to very severe COPD in China.Methods: A Markov model was developed to estimate the cost-effectiveness of TIO/OLO FDC versus TIO in the treatment of COPD from Chinese health system perspective. Four health states were based on 2021 Global Initiative for Chronic Obstructive Lung Disease (GOLD 2021), which included moderate (GOLD II, 50% ≤ FEV1 ≤ 80% of predicted), severe (GOLD III, 30% ≤ FEV1 ≤ 50% of predicted) and very severe (GOLD IV, FEV1 > 30% of predicted) COPD and death. The model simulated in cycles yearly. The indicators of total costs, number of COPD exacerbations, life years (LYs) and quality-adjusted life-years (QALYs) were used as the model output. Costs and outcomes were discounted at a 5% annual rate. A cost-effectiveness analysis was conducted over a 10-year time horizon. The threshold of incremental total cost per unit effectiveness gained (ICER) was 1.5 times of GDP per capita. Uncertainty was assessed by one-way and probabilistic sensitivity analysis.Results: TIO/OLO was 0.007 QALYs more than TIO but 0.012 LYs lower, which increased the total cost by $2268.17 per patient, but the total exacerbations number was less. Incremental cost effectiveness analysis had shown that the ICER exceeded the willingness to pay threshold. Results were robust under most parameter variation, except the parameters of total drug cost of TIO/OLO FDC in univariate sensitivity analyses.Conclusion: Although TIO/OLO FDC could reduce the exacerbation risk, it was not cost-effective, and needed to be repriced.Keywords: tiotropium, olodaterol, cost-effectiveness, chronic obstructive pulmonary disease, COPD, Markov